Biomechanical study of anterior transpedicular root screw intervertebral fusion system of lower cervical spine: a finite element analysis - Ye, Senqi; Ye, Jiachun; Hou, Zhipeng; You, Xinmao; Shen, Shufeng; Zhang, Jihui; Yu, Liang; Gu, Yongjie; Wang, Wei; Zhao, Liujun (Frontiers in Bioengineering and Biotechnology, 2024)
Background: The cervical anterior transpedicular screw (ATPS) fixation technology can provide adequate stability for cervical three-column injuries. However, its high risk of screw insertion and technical complexity have restricted its widespread clinical application. As an improvement over the ATPS technology, the cervical anterior transpedicular root screw (ATPRS) technology has been introduced to reduce the risk associated with screw insertion. This study aims to use finite element analysis to investigate the biomechanical characteristics of a cervical spine model after using the novel ATPRS intervertebral fusion system, providing insights into its application and potential refinement. Methods: A finite element (FE) model of the C3-C7 lower cervical spine was established and validated. After two-level (C4-C6) anterior cervical discectomy and fusion (ACDF) surgery, FE models were constructed for the anterior cervical locked-plate (ACLP) internal fixation, the ATPS internal fixation, and the novel ATPRS intervertebral fusion system. These models were subjected to 75N axial force and 1.0 Nm to induce various movements. The range of motion (ROM) of the surgical segments (C4-C6), maximum stress on the internal fixation systems, and maximum stress on the adjacent intervertebral discs were tested and recorded. Results: All three internal fixation methods effectively reduced the ROM of the surgical segments. The ATPRS model demonstrated the smallest ROM during flexion, extension, and rotation, but a slightly larger ROM during lateral bending. Additionally, the maximum bone-screw interface stresses for the ATPRS model during flexion, extension, lateral bending, and axial rotation were 32.69MPa, 64.24 MPa, 44.07MPa, 35.89MPa, which were lower than those of ACLP and ATPS models. Similarly, the maximum stresses on the adjacent intervertebral discs in ATPRS model during flexion, extension, lateral bending, and axial rotation consistently remained lower than those in the ACLP and ATPS models. However, the maximum stresses on the cage and the upper endplate of the ATPRS model were generally higher. Conclusions: Although the novel ATPRS intervertebral fusion system generally had greater endplate stress than ACLP and ATPS, it can better stabilize cervical three-column injuries and might reduce the occurrence of adjacent segment degeneration (ASD). Furthermore, further studies and improvements are necessary for the ATPRS intervertebral fusion system.